Drug-Induced Heart Failure (Part 2: Mechanisms of Development, Clinical Signs, Differential Diagnosis, Risk Factors, Treatment and Prevention) - O. D. Ostroumova; I. V. Goloborodova (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2020)
Heart failure is a complex clinical syndrome caused by an impaired pumping function of the heart muscle, etiologically associated with cardiovascular disease and, in the vast majority of cases, requiring complex therapeutic regimens and simultaneous prescription of several drugs. To date, we know several classes of drugs (including those used for heart failure) which can induce development/progression of heart failure in both patients with left ventricular dysfunction, and in patients who do not have cardiovascular diseases. The aim of the study was to analyse and systematize data on development mechanisms, as well as methods of prevention and treatment of drug-induced heart failure when using diff erent groups of drugs. It has been established that drug-induced heart failure is most often associated with the use of calcium channel blockers (verapamil, diltiazem, nifedipine), beta-blockers, antiarrhythmic drugs (disopyramide, fl ecainide, propafenone, amiodarone, ibutilide, dofetilide, dronedarone), anthracyclines (doxorubicin) and other antitumor drugs (trastuzumab, bevacizumab, infl iximab), hypoglycemic drugs (thiazolidinediones, saxagliptin, alogliptin), and nonsteroidal anti-infl ammatory drugs, including selective cyclooxygenase-2 inhibitors. The study revealed various mechanisms of heart failure development following drug treatment. In some patients, heart failure development is associated with the cardiotoxic eff ect of a particular drug, in others with adverse eff ects on hemodynamics. Much depends on risks of developing heart failure, including specifi c risks attributable to groups of drugs and individual drugs. The identifi cation of drugs that can contribute to the development/ progression of heart failure, and possible clinical manifestations of drug-induced heart failure, as well as provision of timely information to physicians, and engagement of clinical pharmacologists with the aim of optimizing treatment of patients can facilitate timely diagnosis, treatment and prevention of drug-induced heart failure.